ANALYSING TOURISTS INFLOWS IN A TOURIST DESTINATION-EVIDENCE FROM CROATIA - Baldigara, Tea (The Business of Tourism, 2019)
This study attempts to identify an autoregressive distributed lag model (ADLM) as the data generating process of tourism demand in Opatija approximated by tourist nights. Empirical finding yield to the conclusion that the final model passes all the diagnostic checking and that model fits the data reasonably well throughout the sample period. Quantitative researches of tourism demand and accurate forecasts generating should be at the basis of efficient and effective planning and decision-making. Tourism demand modelling and forecasting, as many studies and researches demonstrated, is a relevant issue that can be helpful to all the stakeholders involved in tourism and hotel industry. Accurate and timely forecast can anticipate future trends and allow to plan, organise and structure tourism capacities and supply more efficiently.
Keywords: Croatia; modelling; tourists nights; tourism demand